L’instrumentum antique du port d’Aizier (Eure) - Malina Robert (Gallia)
Excavations of the port facilities in Aizier (Eure), carried out over several years between 2009 and 2013, led to the discovery of a small instrumentum, composed of 84 objects. The functional and contextual analysis of this corpus sheds light on objects for ordinary and domestic use that circulated in this port or in its surroundings, and also provides a better understanding of the last phases of activity on the port terraces and their subsequent abandonment, as early as during the 3rd c. AD. The objects collected are common and quite varied, as is the case for the instrumentum recovered from nearby estuary sites and also dated to the Early Roman Imperial period. In addition to objects illustrating the everyday life of the port users, certain elements, made of remarkable materials, also make it possible to study small-scale and large-scale networks, within which Aizier must be considered as being a significant crossing point.